2016
DOI: 10.1097/dss.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Readability of Dermatological Postoperative Patient Information Leaflets Across England

Abstract: Most English postoperative dermatological PILs' readability levels exceed recommendations (US grade ≤6). Departmental PILs should be reviewed to ensure that they are comprehensible to their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Guidance from the American Medical Association suggests that PIL readability levels should be ≤ grade 6 US (11–12‐years old) . A recent study demonstrated that less than 30% of 85 UK dermatology postoperative PILs attained this threshold …”
Section: Discussionmentioning
confidence: 98%
“…Guidance from the American Medical Association suggests that PIL readability levels should be ≤ grade 6 US (11–12‐years old) . A recent study demonstrated that less than 30% of 85 UK dermatology postoperative PILs attained this threshold …”
Section: Discussionmentioning
confidence: 98%
“…Patient information leaflets (PILs) are resources that provide education and reassurance to patients, and supplement information provided to them by clinicians during consultations. 1 The British Association of Dermatologists (BAD) website provides PILs that intended to supplement clinic consultations, aiming to ensure access to accurate, reliable and trustworthy information. They are written by dermatologists, and are reviewed and edited by the BAD Therapy and Guideline subcommittee and additionally by a PILs Lay Review Panel.…”
Section: Introductionmentioning
confidence: 99%